Augmented partial diallel cross plans involving two sets of parental lines - Srivastava, Sudhir; Varghese, Cini; Jaggi, Seema; Varghese, Eldho (The Indian Journal of Genetics and Plant Breeding, 2016)
Augmented Partial Diallel Cross (APDC) plans are suitable for situations in which resources are limited where a complete diallel is not feasible, but some lines are believed to be superior and are therefore of prime interest. It is desirable to have these primary lines represent a high proportion of crosses and hence they are crossed with every other lines, but a partial diallel system is used for lines of secondary interest. Here, some classes of APDC plans have been obtained using association schemes of Partially Balanced Incomplete Block (PBIB) designs. Variances pertaining to different groups of interline comparisons have been computed and a list consisting of parameters of plans for useful range has been prepared.